Development of and study of boro-tellurite glasses for optical and radiation shielding applications - M.I. Sayyed; M.H.A. Mhareb; Heryanto heryanto; Yasser Maghrbi (Open Ceramics)
A new group of boro-tellurite glasses (BCa20, BCa17, BCa14, BCa11) was fabricated using the melt quench method for potential radiation shielding and optical applications. The mechanical, optical, and radiation shielding properties were studied with varying oxide compositions. A decrease in B2O3 and CaO content, with increasing TeO2, led to a reduction in elastic modulus and bulk modulus (from 69.638 to 61.331 GPa), as well as a decrease in packing density (0.673 to 0.636). The optical band gap also gradually reduced (from 3.637 to 3.504 eV), while Urbach energy increased (from 0.293 to 0.354 eV). Optical basicity increased, and optical electronegativity decreased, indicating a shift toward ionic bonding and reduced glass stability. Radiation shielding performance improved with the addition of TeO2, as confirmed by the linear attenuation coefficient (LAC) results using Phy-X software. These findings suggest potential for these glasses in radiation shielding and optical material applications.